A window into the vascular endothelium in COVID-19: Nails - Ozge Sevil Karstarli Bakay; Niyazi Cetin; Umut Bakay; Gokhan Cinar; Sule Goksin (Dermatology Practical & Conceptual)
Introduction: Endothelial damage is associated with acute and long-term Coronavirus disease 2019 (COVID-19) complications. Proximal nailfold capillaries are windows for monitoring important microvascular changes associated with endothelial dysfunction.